New records of filarioid nematodes (Nematoda: Filarioidea) parasitic in Australasian monotremes, marsupials and murids, with descriptions of nine new species - Spratt, David M. (Zootaxa, 2011)
Filarioid nematodes (Nematoda: Filarioidea) parasitic in Australasian monotremes, marsupials and murid rodents are described from three genera, Breinlia (Breinlia), Pelecitus and Sprattia. New host and geographic records are presented for 24 previously described species from these genera, a second subgenus, Breinlia (Johnstonema) and an additional three genera, Cercopithifilaria, Monanema and Pelecitus. Nine species are described as new, B. (B.) beveridgei sp. nov. from the peritoneal cavity of Macropus parryi Bennett, B. (B.) bigenera sp. nov. from the peritoneal and pleural cavities of Aepyprymnus rufescens (Gray), Onychogalea fraenata (Gould), O. unguifera (Gould) and possibly Antechinus swainsonii (Waterhouse), B. (B.) dorcopsis sp. nov. from the peritoneal cavity of Dorcopsis hageni Heller and D. luctuosa (D’Albertis), B. (B.) melomyos sp. nov. from the peritoneal cavity of Melomys cf. burtoni, B. (B.) oweni sp. nov. from the peritoneal cavity of Dactylopsila trivirgata Gray, B. (B.) presidentei sp. nov. from the peritoneal cavity of Mesembriomys gouldii (Gray), M. macrurus (Peters) and the pleural and peritoneal cavities of Conilurus penicillatus (Gould), B. (B.) tricondylus sp. nov. from the peritoneal cavity of Macropus rufogriseus banksianus (Quoy & Gaimard), B. (B.) zyzomyos sp. nov. from the peritoneal cavity of Zyzomys woodwardi (Thomas) and Z. argurus (Thomas), and Sprattia spearei sp. nov. from the lung (probably blood vessels) of Isoodon macrourus (Gould) . The female of B. (J.) woerlei from the pulmonary artery, right ventricle and lung cysts of Petrogale brachyotis (Gould) is described for the first time. Breinlia (J.) andersoni Spratt & Varughese, 1975 from the subcutaneous connective tissues of Macropus rufus (Desmarest), M. giganteus Shaw, M. robustus erubescens Sclater and Wallabia bicolor (Desmarest) is placed as a synonym of B. (J.) annulipapillata (Johnston & Mawson, 1938) from the subcutaneous connective tissues of M. dorsalis (Gray), O. fraenata and W. bicolor. In general, filarioids predominate in macropodoid hosts and in the north of Australia.